2005
DOI: 10.1104/pp.105.070318
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Phosphatase AtPP2CA Negatively Regulates Abscisic Acid Signal Transduction in Arabidopsis, and Effects of abh1 on AtPP2CA mRNA  

Abstract: To identify new loci in abscisic acid (ABA) signaling, we screened a library of 35STcDNA Arabidopsis (Arabidopsis thaliana)-expressing lines for ABA-insensitive mutants in seed germination assays. One of the identified mutants germinated on 2.5 mM ABA, a concentration that completely inhibits wild-type seed germination. Backcrosses and F 2 analyses indicated that the mutant exhibits a dominant phenotype and that the ABA insensitivity was linked to a single T-DNA insertion containing a 35STcDNA fusion. The inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
195
0
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(220 citation statements)
references
References 84 publications
13
195
0
10
Order By: Relevance
“…Our data showed that the germination of OE-PYL13 #1 was 56% under 0.5 µM ABA treatment and 14% under 1 µM ABA treatment ( Figure 4E). Consistently, the phenotype of pyl13 mutants is in the same pattern as PP2CA overexpression lines [34], whose seedling establishment is hyposensitive to ABA ( Figure 4F). However, the phenotype of pyl13 mutants is very weak compared with OE-PP2CA transgenic lines, indicating that there are functional redundancy between PYL13 and other PYLs in their inhibition of PP2CA.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Our data showed that the germination of OE-PYL13 #1 was 56% under 0.5 µM ABA treatment and 14% under 1 µM ABA treatment ( Figure 4E). Consistently, the phenotype of pyl13 mutants is in the same pattern as PP2CA overexpression lines [34], whose seedling establishment is hyposensitive to ABA ( Figure 4F). However, the phenotype of pyl13 mutants is very weak compared with OE-PP2CA transgenic lines, indicating that there are functional redundancy between PYL13 and other PYLs in their inhibition of PP2CA.…”
Section: Discussionsupporting
confidence: 66%
“…The PYL13 triple mutant Q38K/ F71L/T135N lost the ABA-independent induction of the RD29B-LUC basal expression ( Figure 4C), suggesting that it is these sequence variations that confer ABAindependent inhibition of PP2CA, HAI2, and HAI3. Moreover, the phenotype of PYL13 overexpression lines is similar to that of pp2ca-knockout mutants [34], whose seed germination is hypersensitive to ABA ( Figure 4E). According to previous reports, the germination of pp2ca-1 mutant was about 45% under 0.5 µM ABA treatment and completely inhibited by 1 µM ABA on day 5 after plating [34].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Currently, at least four Arabidopsis (Arabidopsis thaliana) PP2Cs, ABI1, ABI2, PP2CA, and HAB1 (formerly named AtP2C-HA), are known to regulate ABA signaling. Evidence on their role as negative regulators of ABA signaling has been provided by genetic approaches (Gosti et al, 1999;Merlot et al, 2001;Tahtiharju and Palva, 2001;Gonzalez-Garcia et al, 2003;Leonhardt et al, 2004;Saez et al, 2004;Kuhn, et al, 2006;Yoshida et al, 2006). For instance, the recessive T-DNA insertion mutant hab1-1 shows ABAhypersensitive inhibition of seed germination and enhanced ABA-mediated stomatal closure (Leonhardt et al, 2004;Saez et al, 2004).…”
mentioning
confidence: 99%